A intersetorialidade das políticas de saúde e de assistência social no sistema de atenção domiciliar em Franca/SP - Martins, Ariana Siqueira Rossi [UNESP] (2015)
The increase of the aged in the world and in Brazil has affected the different care services to this population, imposing a reordering of public policies so that they meet in full the needs of this specific demand. It has been much discussed the issue of healthy and active aging, but we must also discuss and study the stage of life in the aging process, when it no longer has the mobility and autonomy for daily activities. The dependence on others to perform daily activities and care (personal hygiene, the act of feeding, changing clothes, taking medication, etc.) causes changes in the routine of the aged person, as in the routine of his family, who need to ensure the permanent presence of a caregiver and all the necessary resources for the realization of care. As an objective of this work, we propose to know the resources and services offered to the elderly by health policies and social assistance in the city of Franca / SP, as also check how is the form of access. For this, we used a qualitative approach research through interviews with managers of health policies and social welfare of the municipality, representatives of municipal councils, professional charities, voluntary caregivers and family caregivers of bedridden elderly. We use the dialectical method as a theoretical foundation, for enabling the scope of the complexity and totality that the researched topic shows. As a result, we found that although there are different resources and services provided by health policies and social assistance, has still been insufficient and inefficient in some respects, such as the fragmentation of services and policies, and difficult access to them through bureaucratic and unconnected processes. The practice of an intersectoral and interdisciplinary work points to the possibility of a humanized service, able to contemplate the different aspects related to the care and well-being that the elderly bedridden at home needs. Social work through its...